PENGGUNAAN MODEL PEMBELAJARAN VAK (VISUALIZATION AUDITORY AND KINESTETIC) DENGAN METODE PENGULANGAN DAPAT MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM TENTANG ISTILAH-ISTILAH DALAM MUAMALAH EKONOMI SYARIAH PADA SISWA KELAS XI KULINER 2 SMKN1 KOTA TASIKMALAYA - Nuraida, Dede (LPPM Universitas Bina Bangsa, 2024)
PAI learning at school is very important for students, which is a systematic and pragmatic effort to help students so that they live according to Islamic teachings. This research aims to: determine whether there is an increase in Islamic Religious Education learning outcomes after using the VAK learning model which involves learning modalities and repetition methods. Apart from that, this research aims to determine students' motivation and activeness in PAI learning after using the VAK learning model which involves learning modalities and repetition methods. To find out the responses or attitudes that emerge in Islamic Religious Education learning using the VAK learning model which involves learning modalities and repetition methods. This research uses Classroom Action Research (PTK) which is carried out in 2 cycles. The research instrument uses Observation and Observation Tests. Student data was obtained from 37 student research subjects, 4 men and 33 women. Based on the research results, it was concluded that PAI learning about Muamalah terms in Sharia Economics uses the VAK (Visualization, Auditory, Kinesthetic) learning model with the repetition/repetitive method starting from proper planning, implementation in accordance with research procedures, as well as observations of the resulting activities. and student learning outcomes have improved very well. The average student activity score in cycle I was 44 or around 58.67% who reached the KKM, increasing in cycle II to 84 or around 100% of students who reached the KKM. Likewise with student learning outcomes, student learning outcomes in cycle I were 44 or around 58.67% who reached the KKM, increasing in cycle II to 84 or 100% of students who reached the KKM